Media Promosi Dan Informasi Pada PT. Gardena Karya Anugrah Berbentuk Video Company Profile - Mukti Budiarto; Ulis Bella; Nita yuliani (UNIVERSITAS RAHARJA, 2018)
Currently open access to information allows information to be easily obtained anytime and anywhere. Information is important, because with information people will get everything they want. Dissemination of information spread through print media atupun electronic media in the form of multimedia, from media that community can get information. PT. Gardena Karya Anugrah is one furniture product company located at Jl. Adi Sucipto No.128 Kelurahan Pajang, Tangerang City District Object, PT. Gardena Karya Anugrah which is not quite long enough in the form, PT. Gardena Karya Anugrah which is fairly new and still use oral media, writings, magazines and website, then the PT. Gardena Karya Anugrah Requires Media Company Profile to support the promotion of PT. Gardena Karya Anugrah To inform the general public especially for prospective customers interested in ordering various furniture PT. Gardena Karya Anugrah. In the concept there are preproduction, production and postproduction stages. In order to produce video-based media design company profile communication and good information and quality applications used Adobe Photoshop CS6 support, Adobe Premier CS6 and Adobe Corel Video Studio X5.